Antonio Gramsci on Italian Futurism: Politics and the Path to Modernism. (2nd October 2018) - Gounalis, Nicole
ABSTRACT: This article catalogues and contextualizes Antonio Gramsci's pre-prison newspaper articles on Futurism, as well as each reference to Futurism in the Quaderni del carcere, to show that Gramsci is equally attentive to aesthetic and political concerns in his evaluation of the movement, and that they present an evolving but coherent view. This perspective is conditioned by awareness of Futurism's interventions in the context of efforts at creating a 'contemporary romanticism', to use Gramsci's term. Furthermore, this view is predicated on Gramsci's insistence that Futurism fails in its aim to create a national(ist) art and culture because its leader, F.T. Marinetti, cannot overcome his attachment to the Italian high literary tradition, and the role of the artist within it.